Principles of financial regulation - Armour, John (Oxford : Oxford University Press, 2016)
The financial crisis of 2007-9 revealed serious failings in the regulation of financial institutions and markets, and prompted a fundamental reconsideration of the design of financial regulation. It is now clear that regulation must focus on the financial system as a whole, but this poses significant challenges for regulators. This volume describes how to address those challenges. Examining the subject from a holistic and multidisciplinary perspective, it considers the underlying policies and the objectives of regulation by drawing on economics, finance and law methodologies.
This edition previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 5, 2016).
Keywords: Financial institutions -- Law and legislation; Law; Laws of specific jurisdictions & specific areas of law